Advance of the traceability of bovine and bufalino cattle in Colombia (2019)
The purpose of this document is to show the reader the importance of animal traceability focused on bovine and buffalo species, which has been implemented in Colombia since 2004, in order to meet and ensure the safety of food of animal origin, as well as preventing the spread of animal diseases with zoonoses in human beings, evaluating the advances that the country has had in the concept of traceability, as well as its health and commercial benefits for citizens who are dedicated to the production of cattle and buffalo in Colombia.